Retrofitting of an Existing Structure Using NDT Test and Analysis Tool STAAD.Pro : A Review - Abhishek Kumar Pandey; Irfan Khan (International Journal of Scientific Research in Civil Engineering, 2024)
In this research we will examine an existing R.C.C. culvert in this study, whose strength is low as a result of age and other factors like increased loading, discharge rate, etc. In this study, the N.D.T. test (rebound hammer) is used to determine the structure's current strength. Then, using the staad.pro analysis tool, we determine the best way to strengthen the structure by retrofitting it using its existing strength and measure the variation in strength after retrofitting. Here, I compare the strength of the original and the retrofitted structures and use S.O.R. CPWD 2017 rates to support the necessary cost for strengthening the structure.
Keywords: Discharge; Staad.pro; Retrofitting; N.D.T.; Culvert; I.R.C. Loading; Cost Analysis; Fresh and Hardened Test on Concrete